2015
DOI: 10.1016/j.jpowsour.2014.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotube spaced graphene aerogels with enhanced capacitance in aqueous and ionic liquid electrolytes

Abstract: Carbon nanotube spaced graphene aerogel has been prepared by a hydrothermal method and used for supercapacitor applications. The specific surface area and specific capacitance can be controlled by tuning the amount of added carbon nanotubes. The as-prepared composite aerogel keeps the advantage of aerogel structure in providing macropores to ensure electrodes fast wetted by the electrolyte ions, and also possesses additional mesopores created by the carbon nanotube spacers for more ion adsorption. Benefited fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…For instance, freestanding 3D graphene with porous structures not only facilitates the access of electrolyte to its surface but also provides electrically conductive channels for the active materials to anchor on [13]. At present, a number of strategies for the preparation of 3D graphene layers and 3D graphenebased composites have been reported [14][15][16], such as 3D graphene layers produced by the reduction of a graphene oxide (GO) suspension in a forced-convection oven [17,18] networks derived from direct-templated chemical vapor deposition (CVD) [19,20], and strutted graphene grown by substratefree sugar blowing [21,22]. However, 3D graphene layers via hydrothermal reduction still suffer heterogeneous inter-sheet connections and high junction resistances [23].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, freestanding 3D graphene with porous structures not only facilitates the access of electrolyte to its surface but also provides electrically conductive channels for the active materials to anchor on [13]. At present, a number of strategies for the preparation of 3D graphene layers and 3D graphenebased composites have been reported [14][15][16], such as 3D graphene layers produced by the reduction of a graphene oxide (GO) suspension in a forced-convection oven [17,18] networks derived from direct-templated chemical vapor deposition (CVD) [19,20], and strutted graphene grown by substratefree sugar blowing [21,22]. However, 3D graphene layers via hydrothermal reduction still suffer heterogeneous inter-sheet connections and high junction resistances [23].…”
Section: Introductionmentioning
confidence: 99%
“…116 Moreover, carbonization process is reported to impact microstructure of CAs, as some micropores take place during pyrolysis of RF systems. [93][94][95]120 This broad peak is related to the non-crystalline π-π stacked graphene nanosheets in the structure of GCNTAs. 111 Formation steps, morphology and structural properties of selfassembled GAs, prepared through reduction process in the presence of sodium ascorbate as reducing agent at 90°C, are presented in Figure 16.…”
Section: Structural Characteristics Of Carbon Aerogelsmentioning
confidence: 96%
“…111 Formation steps, morphology and structural properties of selfassembled GAs, prepared through reduction process in the presence of sodium ascorbate as reducing agent at 90°C, are presented in Figure 16. Shao et al 120 suggested that a sandwich morphology form during the hydrothermal process of GO nanosheets with SWNTs stacked between GO nanosheets. [117][118][119] However, further hydrothermal reduction results in more reduction of GO nanosheets and more π-π conjugation between graphene structures.…”
Section: Structural Characteristics Of Carbon Aerogelsmentioning
confidence: 99%
“…And, the equivalent series resistance (ESR) of PNGC is obtained from the x intercept of the Nyquist plots with two-electrode system in Fig. S2 [48], which is 2.98 , obviously smaller than several carbon materials reported with similar test method [3,49]. Meanwhile, compared with arcs of rGO at high frequency, those of GC, NGC and PNGC are inconspicuous, because of their low electronic resistance [50].…”
Section: Electrochemical Performancementioning
confidence: 98%